Level of Knowledge and Adoption of Water Saving Technologies by farmers in Sri Muktsar Sahib District of Punjab - Singh, Dalbeer; Kaur, Dr. Prabhjot; Kaur, Dr. Tarundeep (International Journal of Bio-resource and Stress Management, 2017)
A study was undertaken in the year 2015−16 to find the adoption and knowledge level of farmers regarding selected recommended water saving technologies (Direct seeded rice, Zero tillage in wheat, Laser leveler and Tensiometer) in Sri Muktsar Sahib district of Punjab. A total of 150 farmers were randomly selected from 8 villages of two blocks based on the probability proportion to the number of farmers in each village. Data were collected by personally interviewing the farmers. It was found that majority of the farmers were of the middle age group of 38−50 years, had gained education of matriculation level and fell in the category of medium (10−25 acres) operational land holdings. Majority of the respondents belonged to low mass media exposure, extension contacts and participation in extension activities It was found that majority of the respondents (58%) had low knowledge level about direct seeded rice, whereas about 57% and 49% of respondents had medium knowledge about zero tillage and laser leveller respectively. The adoption of laser leveler was appreciably high whereas adoption of DSR and ZTW was found to be comparatively quite low. Among the DSR adopters, about 90% had applied the recommended pre emergence herbicide for weed control. In case of ZTW, none of adopter had applied the pre sowing/emergence herbicide. Majority of respondents in both DSR (95.24%) and ZTW (79.31%) had applied a higher dose of nitrogenous in fertilizer than recommendations of PAU, Ludhiana due to lack of knowledge.